Твори Лесі Українки у світлі рампи сучасного театру - Puszak, Lubomir (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The paper continues an earlier work on the stage production of dramatic works by Lesya Ukrainka in Ukrainian theatres. It presents the overview of stage productions put on in the years of 2012 to 2016, as well as productions, which had been staged earlier but are still performed on the stage. The study is based on the overview and the analysis of publications in Ukrainian theatre periodicals available online, as well as on the data presented on the websites of Ukrainian theatres. The analysis of the material leadsto the conclusion that Lesya Ukrainka’s dramatic works included in the current listof productions of Ukrainian theatres (drama, opera and ballet, experimental, puppet, and amateur ones) hold the attention of theatre directors, who take both modern and traditional approaches to staging her plays. Productions of the fairy drama Forest Songare the most frequent to be put on stage.